The Implementation Of Scientific Approach In Teaching English At The 8th Grade Of SMP Negeri 1 Colomadu In 2014/2015 Academic Year - Pamilih Guntoro, Tatag; , Aryati Prasetyarini, S.Pd, M.Pd; , Siti Fatimah, S. Pd, M. Hum (2015)
Scientific is a modern term in learning world to motivate and develop the learners.Using scientific approach, it is expected that the studentscan think scientifically, logically, critically and objectively in accordance with the facts. This research aims at finding out the implementation of scientific approach in teaching English at SMP Negeri 1 Colomadu, specifically it is to describethe learning objective, instructional material, method implemented by the English teacher, the procedure of the method applied, and the evaluation and problems faced by the teacher in implementing scientific approach in teaching English at SMP Negeri 1 Colomadu, in 2014/2015 academic year. The data of this research are collected in the form of field notes, lesson plan, syllabus, assessment form, and interview notes. The writer takes the English teacher and eighth grade students of SMP Negeri 1 Colomaduas the subject of this research. The writer uses descriptive qualitative research especially spiral research in analyzing the data. The result of the study shows that the teacher used inquiry-based learning as the method in the implementation of scientific approach. The English teacher of the eighth grade students at SMP Negeri 1 Colomadu uses authentic assessment in the evaluation.